Narrating survival: Dina Gottliebova in conversation with Hilary Helstein. Issue 4 (1st October 2020) - Hillman, Susanne; Kuehn, Joanna
ABSTRACT: In this article the authors analyze the Shoah Foundation's video testimony of the Holocaust survivor Dina Gottliebova (1923–2009). Based on a thorough examination of Gottliebova's audiovisual narrative performance, the authors argue that video testimonies are not sources of information that can be taken as inherently factual; rather, they illuminate the narrative self-fashioning and agency of a specific individual in dialogue with a specific interviewer. As subjective retellings affected by the passage of time and the bias of the participants, they are marked by narrative stumbling blocks that challenge preconceived notions about the Holocaust and help undermine canonical narratives.